2013
DOI: 10.1002/jclp.22030
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Cognitive Behavior Therapy for Co‐Occurring Insomnia and Depression Symptoms in Older Adults

Abstract: Objective Telehealth has proven effective with a wide range of disorders, but there is a paucity of data on the use of telehealth using cognitive-behavior therapy (CBT) with late-life insomnia and depression. This pilot study was designed to examine the feasibility and effectiveness of using telehealth to treat older adults with comorbid insomnia and depression living in rural Alabama. Method Five patients received 10 sessions of CBT for insomnia and depression. Patients were engaged in treatment via Skype f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 34 publications
2
85
0
1
Order By: Relevance
“…We classified twelve (44%) of the included studies as "feasibility studies" (Table 3); [5][6][7][8][9][10][11][12][13][14][15][16][17] nine (33%) as "clinical studies" (Table 5); [18][19][20][21][22][23][24][25][26] and six articles (22%) as "clinical education" studies (Table 7). 6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment.…”
Section: Study Purposementioning
confidence: 99%
See 2 more Smart Citations
“…We classified twelve (44%) of the included studies as "feasibility studies" (Table 3); [5][6][7][8][9][10][11][12][13][14][15][16][17] nine (33%) as "clinical studies" (Table 5); [18][19][20][21][22][23][24][25][26] and six articles (22%) as "clinical education" studies (Table 7). 6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment.…”
Section: Study Purposementioning
confidence: 99%
“…6,[27][28][29][30][31] Study design Nine (33%) of the included studies had a controlled design, with six (22%) having random assignment of participants to Skype or to a control, 10,12,13,19,21,25 with the remaining three studies (11%) having non-randomised assignment. 8,22,30 Five studies (19%) reported a pre-test / post-test design, 9,11,16,26,28 while three (11%) reported method-comparison studies. 14,20,24 Qualitative designs were …”
Section: Study Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Another way to increase access to therapistdelivered CBTI that we have not yet discussed involves the use of telehealth services to extend the reach of already trained providers to patients with no or limited access to an office visit due to logistical factors, distance from available CBTI specialists, or limitations to mobility. Initial evidence suggests that this is an effective mode of delivery [32,33]. However, at the time of this writing, telehealth delivery and validated internetdelivered CBTI and technology are not covered by most commercial health insurance companies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high satisfaction (Choi et al, 2014a;King et al, 2014;Storch et al; and a strong therapeutic alliance (King et al;Lichstein et al, 2013;Yuen et al, 2013) have been observed. With respect to feasibility, patients have found the modality to be convenient, but technical difficulties (Choi et al, 2014b;King et al, 2014;Lichstein et al, 2013;Yuen et al, 2013) and challenges reading body language (Lichstein et al, 2013;Storch et al, 2011) are common. Despite preliminary evidence, research on the efficacy and feasibility of VoIP-delivered therapy is still rather limited; and the validity and reliability of administering clinician-rated measures via this modality have yet to be assessed.…”
mentioning
confidence: 98%